Protective Role of Kallistatin in Vascular and Organ Injury - Chao, Julie (Hypertension, 2016)
Kallistatin is an endogenous protein that exerts pleiotropic effects, including vasodilation and inhibition of angiogenesis, inflammation, oxidative stress, apoptosis, fibrosis, and tumor progression. Through its two functional domains – an active site and a heparin-binding site – kallistatin regulates differential signaling pathways and a wide spectrum of biological functions. Kallistatin's active site is key for inhibiting tissue kallikrein activity, and stimulating the expression of endothelial nitric oxide synthase (eNOS), sirtuin 1 (SIRT1) and suppressor of cytokine signaling 3 (SOCS3). Kallistatin via its heparin-binding site blocks signaling pathways mediated by growth factors and cytokines, such as vascular endothelial growth factor (VEGF), tumor necrosis factor-α (TNF-α), high mobility group box-1 (HMGB1), Wnt, transforming growth factor-β (TGF-β), and epidermal growth factor (EGF). Kallistatin gene or protein delivery protects against the pathogenesis of hypertension, heart and kidney damage, arthritis, sepsis, influenza virus infection, tumor growth and metastasis in animal models. Conversely, depletion of endogenous kallistatin by neutralizing antibody injection exacerbates cardiovascular and renal injury in hypertensive rats. Kallistatin levels are markedly reduced in rodents with hypertension, sepsis, streptozotocin-induced diabetes, and cardiac and renal injury. Kallistatin levels are also diminished in patients with liver disease, septic syndrome, diabetic retinopathy, severe pneumonia, inflammatory bowel disease, and obesity, prostate and colon cancer. Therefore, circulating kallistatin levels may serve as a new biomarker for human diseases. This review summarizes kallistatin's protective roles and mechanisms in vascular and organ injury, and highlights the therapeutic potential of kallistatin for multiple disease states.